Effects and after-effects of the common cold and influenza on human performance - Smith, A P; Tyrrell, D A; al-Nakib, W; Barrow, P G; Higgins, P G; Leekam, S; Trickett, S (Neuropsychobiology, 1989)
Volunteers who develop a cold following virus challenge were significantly slower on choice reaction time tasks than those with no illness. This effect was still observed after the clinical symptoms had gone. In contrast to this, influenza illnesses only impaired performance in tasks in which subjects were uncertain where the target stimulus would appear. These results demonstrate that the CNS effects of respiratory virus infections depend on the type of virus, and that performance impairments may remain even after the symptoms of a cold have gone.